2019
DOI: 10.1158/1078-0432.ccr-18-3571
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the Evolution and Progression of Small-Cell Lung Cancer by Single-Cell Sequencing of Circulating Tumor Cells

Abstract: Purpose: Genomic analyses of small-cell lung cancer (SCLC) are limited by the availability of tumor specimens. This study aimed to investigate the suitability of single-cell sequencing of circulating tumor cells (CTC) as a method of inferring the evolution and progression of SCLCs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 34 publications
4
63
0
Order By: Relevance
“…In CTCs, genome-wide CNVs were found to be highly reproducible from cell to cell within the same individual and across different lung cancer patients with same pathological subtypes [43,45]. This is consistent with homogeneity found in CTCs from SCLC [42,46] and colorectal cancer patients [45].…”
Section: Ctc Heterogeneity and Clinical Impactsupporting
confidence: 71%
“…In CTCs, genome-wide CNVs were found to be highly reproducible from cell to cell within the same individual and across different lung cancer patients with same pathological subtypes [43,45]. This is consistent with homogeneity found in CTCs from SCLC [42,46] and colorectal cancer patients [45].…”
Section: Ctc Heterogeneity and Clinical Impactsupporting
confidence: 71%
“…The expression characteristics of CTC may be higher than those of other cancer types. Su et al [ 52 ] performed whole genome sequencing detection of CTC in 10 patients with small-cell lung cancer who received standard chemotherapy regimens of etoposide + platinum (cisplatin, neda platinum or carboplatin). Amongst the 91 CTCs selected, the CNA spectra of patients’ CTC were found highly consistent, which also confirmed that CTC could be used as an ideal sample for clinical correlation analysis of patients with cancer.…”
Section: Single-cell Sequencing Of Ctc To Predict Drug Resistance In mentioning
confidence: 99%
“…With advances in next-generation sequencing (NGS) and single-cell sequencing (SCS) technologies, scientists can obtain the complete genome of a CTC and compare it with corresponding primary and metastatic tumours [113,120]. Molecular analysis of CTCs has predicted chemosensitive or refractory disease and subsequent patient outcomes [121].…”
Section: Advances In Biomarkersmentioning
confidence: 99%
“…Molecular analysis of CTCs has predicted chemosensitive or refractory disease and subsequent patient outcomes [121]. With specific focus on copy number aberrations (CNAs), Su et al showed utility of single cell sequencing of CTC with regards to survival, chemotherapy response, and heterogeneity by tracing allele specific CNAs in CTCs isolated at different timepoints of chemotherapy [120]. Phenotypic heterogeneity was also found with regards to expression of Bcl-2, CK, Vim, and M30 [120].…”
Section: Advances In Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation